Performance evaluation of the automated nucleated red blood cell count of five commercial hematological analyzers. (8th October 2017) - Da Rin, G.; Vidali, M.; Balboni, F.; Benegiamo, A.; Borin, M.; Ciardelli, M. L.; Dima, F.; Di Fabio, A.; Fanelli, A.; Fiorini, F.; Francione, S.; Germagnoli, L.; et al.
Abstract: Introduction: Recent automated hematology analyzers (HAs) can identify and report nucleated red blood cells (NRBC) count as a separate population out of white blood cells (WBC). The aim of this study was to investigate the analytical performances of NRBC enumeration on five top of the range HAs. Methods: We evaluated the within‐run and between‐day precision, limit of blank (LoB), limit of detection (LoD), and limit of quantitation (LoQ) of XE‐2100 and XN‐module (Sysmex), ADVIA 2120i (Siemens), BC‐6800 (Mindray), and UniCel DxH 800 (Beckman Coulter). Automated NRBC counts were also compared with optical microscopy (OM). Results: The limits of detection for NRBC of the BC‐6800, XN‐module, XE‐2100, UniCel DxH 800, and ADVIA 2120i are 0.035×10 9 /L, 0.019×10 9 /L, 0.067×10 9 /L, 0.038×10 9 /L, and 0.167×10 9 /L, respectively. Our data indicated excellent performance in terms of precision. The agreement with OM was excellent for BC‐6800, XN‐module, and XE‐2100 (Bias 0.023, 0.019, and 0.033×10 9 /L, respectively). ADVIA 2120i displayed a significant constant error and UniCel DxH 800 both proportional and small constant error. Conclusion: Regards to NRBC counting, the performances shown by BC‐6800, XN‐module, and XE‐2100 are excellent also a low count, ADVIA 2120i and UniCel DxH 800 need to be improved.